Hubungan Komunikasi Pemasaran di Media Sosial dengan Minat Berkunjung ke The Park Jabar - Galih Nugraha; Mochammad Rochim (UNISBA Press, 2024)
Abstract. The impact of technological developments in the field of communication and information has formed a digital society. Thus, social media, which is one form of digital media, can be utilized by business managers in the tourism sector to launch their marketing strategies. The Park Jabar is no exception, as one of the tourist destinations in Bandung. The content entitled